Estudo fitossociológico como estratégia para bioprospecção e conservação de espécies de área de restinga - BELFORT, Luciana (2018)
The restingas extend along the entire Brazilian coastal region, forming a mosaic of herbaceous of strata of herbaceous, shrub and tree composition. Due to the diversity of vegetation, territorial extension and constant threats to biodiversity, studies have been intensified to know the richness the richness, diversity and structural arrangement of the restingas' vegetation through phytosociological phytosociological studies. The restinga vegetation is constantly subjected to environmental conditions that environmental conditions that favor the increased production of bioactives of pharmacological importance. Therefore, it is believed that the use of the ecological Importance Value (VI) parameter is an interesting strategy for the selection of species for bioprospecting. The present dissertation brings a chapter that deals with toxic evaluation and tumoricidal activity of the plant species species of higher VI from a sandbank area. To meet the proposed analyses, a phytosociological phytosociological survey was carried out to determine the species with the highest VI, using the of points-squares. After the ranking, with the leaves of the five selected species were prepared hydroethanolic extracts to perform in vitro tests with 3-methyl bromide 3-methyl-[4-5-dimethylthiazol-2-yl]-2.5 diphenyltetrazolium bromide (MTT) assay. The toxicity of the extracts was determined by the viability of macrophages of the Raw 264.7 strain and the tumoricidal was determined by the viability of human prostate (DU- 145) and breast (MCF- 145) tumor cells. 145) and breast (MCF-7) tumor cells, both with cells incubated in the presence of extracts at concentrations concentrations of 65.5, 125, 250 and 500 μg/mL for 24h. The species that stood out in the community structure with higher VI, and therefore selected for bioprospecting were Astrocaryum vulgare Mart., Attalea speciosa Mart. ex Spreng., Himatanthus drasticus (Mart.) Plumel, Chamaecrista ramosa (Vogel) H.S. Irwin & Barneby and Eugenia biflora (L.) DC. represented 75.5% of the total VI for the area. The results of the viability of Raw 264.7 cells showed that, in general, the leaves of the selected species showed low toxicity to toxicity to murine macrophages and showed no significant activity against human tumor cells in vitro. tumor cells in vitro. Although the results of biological activity were not statistically significant statistically significant, the plant species selection strategy tested in this work proved to be proved to be useful for choosing promising species for bioprospective investigations. bioprospective investigations. Finally, considering the value of importance, the species that, despite being dominant in restinga, are exposed to threats to biodiversity common to this ecosystem, should ecosystem, should support further analyses to contribute to the conservation and maintenance of this ecosystem. and maintenance of this ecosystem.